Object Locator Using RFID Technology for Blind People - Qasrawi, Hiba; Awawdeh, Yaman (Palestine Polytechnic University, 2017)
Object locator using RFID technology is a practical method aim to find lost things for blind people. The focus is on resolving the situation that faces us almost every day. This is forgetting where we put our things or misplaced things, so spending a lot of time to find it, on average about 15 minutes each day searching for items like cell phones, keys and remote control. Now what if this faces blind people you could imagine how much this will be hard for them especially if there is no one to help them. To overcome this irritating problem we built a system based on RFID (radio frequency identification) .The RFID technology work on the principle of sending electromagnetic wave from the reader to tags, this tags was attached to the objects that the blind person want to find. The design of the system depends on the raspberry pi that used for processing and controlling of the reader. Firstly, the blind will say the name of the wanted object. Secondly, the reader will begin scanning the tags in its range. Finally when the selected tag is detected a voice response indicates that the object is found will say to the blind. We installed another reader connected to raspberry pi in other place to detect the object that placed out of the range of the first reader and the two readers will communicate to each other. The system provided the blind an easy way to search through voice orders describe the wanted object. Keywords: RFID, reader, tag, raspberry pi
CD, no of pages 99, 30144, 9/2017طاقة, in the store
Keywords: Object Locator Using RFID Technology for Blind People